Edukasi dan Keterampilan tentang Acupressure Massage untuk Meningkatkan Fokus dan Konsentrasi Belajar pada Sisiwa SMAN 1 Kramat Kabupaten Tegal - Rahmanindar, Nora; Qudriani, Meyliya; Arti, Tias Dwi; Riski, Intan Cristi Mayasari; Hidayah, Seventina Nurul; Zulfiana, Evi; Furqoni, Laduniyah; Awaliyah, Afidatul (Universitas Muhammadiyah Semarang, 2024)
Acupressure massage to brighten the brain is a stimulation technique to improve the flow of blood vessels, nerves and meridians leading to the head and brain. Massage on students will have a positive impact because students will feel more ready to receive stimulus so they can learn more quickly, and this is closely related to the development that occurs in the brain. In reality, there are still many students who often have difficulty concentrating when faced with more complex subject matter, for example counting, memorizing, and so on. The aim of this service is to provide students with skills and understanding on how to increase focus and concentration in learning. They can choose acupressure massage therapy to increase students' focus and concentration in a safe manner so as to help with the school exam process. The service will be carried out on 13-14 November 2023, at SMAN 1 Kramat, for 40 students in classes X and XI.